Optimizing Invoice Management: A Case Study of PT. Madina Mitra Teknik's Transition to a Laravel-Based Information System - Diantoro, Karno (Indonesian Scientific Publication, 2023)
One business that engages in trading goods and services is PT. Madina Mitra Teknik. During the observations, Microsoft Excel was still used for manual invoice recording, even though the collection division had access to computer tools that may facilitate collection efforts. The goal of this research is to design an invoice-recording information system that can help manage existing invoices at PT. Madina Mitra Teknik in the collection section with development using the Laravel framework. Currently, no information system helps record invoices and their progress as they are issued and incoming payments, so the process of making reports takes time. The research process includes analysis, design, coding, and testing. The waterfall development method is employed. The output of this study is an invoice recording system, and the results of the black box testing show that every function has operated as intended. To ensure that the invoice recording information system is appropriate for use and implemented to support the invoice management process in the PT collection section, Madina Mitra Teknik conducted a portability test using three different browsers and found that all aspects of the system could be accessed without any issues.